Nexus between Economic, Trade and Financial Liberalization of European Economies - Saifullah Niaz; Waqas Ahmed; Syed Zia Hussain Shah (International Journal of Business and Economic Affairs, 2025)
This study explores the relationship between economic, trade and financial liberalization, with remittances, and real exchange rate across 12 European countries. Using panel data from 2000 to 2023 the study employs various econometric techniques including fixed and random effects models, Panel Auto Regressive Distributive Lag Model, and dynamic Granger causality. The results reveal that real exchange rate and remittances significantly influence economic liberalization in both the short and long run. Real exchange rate depreciation steadily reduces economic liberalization, while remittances also show a negative long-run effect, suggesting inefficiencies in their use. Trade liberalization and financial liberalization possesses short-run positive effects. The error correction term confirms a stable long-run relationship among the variables. The study concludes that specific policy changes such as keeping exchange rates stable, making better use of remittances, and improving institutional policies to ensure that liberalization efforts lead to long term economic liberalization.